Arthroscopy versus nonoperative treatment of symptomatic femoroacetabular impingement syndrome: A protocol for systematic review and meta-analysis. Issue 49 (4th December 2020) - Kim, Chul-Ho; Moon, Jun-Ki; Yoon, Jae Youn; Lee, Sunhyung; Kim, Won Jun; Kim, Han Soul; Lee, Soong Joon; Yoon, Pil Whan
Abstract: Background: Presently, hip arthroscopy is a widely adopted surgical intervention for the treatment of femoroacetabular impingement (FAI). However, there is insufficient evidence regarding which between arthroscopy and nonoperative treatment is more optimal for symptomatic FAI. Methods: MEDLINE, Embase, Web of Science, and the Cochrane Library were systematically searched for studies that compared arthroscopy and nonoperative interventions for FAI treatment from inception to August 4, 2020. We included studies that directly compared surgical and nonsurgical treatment for symptomatic FAI and excluded those that did not use arthroscopic treatment as a surgical technique and studies performed on patients with concomitant diagnoses instead of pure FAI. We compared the following clinical outcome scores at 6 and 12 months of follow-up: International Hip Outcome Tool 33 (iHOT-33), hip outcome score (HOS), EuroQol-visual analog scale (EQ-VAS), modified Harris hip score (mHHS), and nonarthritic hip score (NAHS). Results: Five studies totaling 838 patients were included in the qualitative and quantitative synthesis; 382 patients underwent hip arthroscopy, and 456 patients were treated by nonoperative interventions. At 6 months of follow-up, there were no statistically significant differences in iHOT-33 ratings (mean difference [MD] = 7.92, P  = .15), HOS (MD of HOS-ADL = 5.15, P  = .26 and MD of HOS-Sports = 2.65, P  = .79, respectively), and EQ-VAS (MD = 1.22, P  = .76) between the 2 treatment strategies. At 12 months of follow-up, the arthroscopy group had a greater mean improvement in iHOT-33 score than the conservative treatment group (MD = 8.42, P  = .002), but there was no difference between the groups in terms of mHHS rating (MD = −0.24, P  = .83) and NAHS (MD = −2.08, P  = .09). Conclusion: Despite arthroscopy being associated with significantly superior iHOT-33 scores after 12 months of follow-up, we were unable to discern the difference between the treatment strategies using other scoring methods, such as HOS, EQ-VAS, mHHS, and NAHS. Further studies will be needed to conclusively determine if 1 strategy is superior to the other for treating FAI.